2020
DOI: 10.3390/ijms21134758
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Signaling in Ocular Neovascularization

Abstract: Vasculogenesis and angiogenesis play a crucial role in embryonic development. Pathological neovascularization in ocular tissues can lead to vision-threatening vascular diseases, including proliferative diabetic retinopathy, retinal vein occlusion, retinopathy of prematurity, choroidal neovascularization, and corneal neovascularization. Neovascularization involves various cellular processes and signaling pathways and is regulated by angiogenic factors such as vascular endothelial growth factor (VEGF) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 175 publications
0
12
0
Order By: Relevance
“…Additionally, NF-κB, an essential regulator of IL-6 and PGE2, and COX-2, whose selective antagonist inhibits subretinal fibrosis, are both further crucial regulators of CNV. [ 19 , 218 , 219 , 220 ]. Compelling evidence also suggests that ocular infiltration of a specific type of macrophages (M2 macrophage) via the LTB4-BLT1 signaling pathway is intimately involved in the development of laser-induced CNV [ 69 ].…”
Section: Pathology Of Age-related Macular Degeneration (Amd) and Imentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, NF-κB, an essential regulator of IL-6 and PGE2, and COX-2, whose selective antagonist inhibits subretinal fibrosis, are both further crucial regulators of CNV. [ 19 , 218 , 219 , 220 ]. Compelling evidence also suggests that ocular infiltration of a specific type of macrophages (M2 macrophage) via the LTB4-BLT1 signaling pathway is intimately involved in the development of laser-induced CNV [ 69 ].…”
Section: Pathology Of Age-related Macular Degeneration (Amd) and Imentioning
confidence: 99%
“…Lipids provide energy storage and serve as structural components of cell membranes, ensuring the homeostasis of these barriers. Lipids can also act as signaling molecules, influencing many processes, including gene expression [ 18 , 19 ]. Long-chain n-3 (also called omega-3) fatty acids are particularly essential for the normal growth and neural development of the brain and eye [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, our analysis of retinal imaging in MacTel patients indicated that low SM correlated with retinal neovascularization. Though no direct correlations have previously been described between neovascularization and SM, others have observed associations between ceramides and sphingosine 1-phosphate with ocular neovascularization and angiogenesis 44 . These results, combined with the reduction in glycosylated sphingolipids, further link MacTel pathogenesis to dysregulation of membrane lipids 45 .…”
Section: Discussionmentioning
confidence: 90%
“…In the previous study, it histologically revealed that lipid was packed underneath PED 11 . It has been considered that lipid signaling promotes the development of neovascularization in ocular tissues 12 . Given that lipid volume is associated with signal strength, it might be reasonable that PED width is associated with MNV.…”
Section: Discussionmentioning
confidence: 99%